E.O. Smirnova on moral education of children - Burlakova, Irina A. (Nat͡s︡ionalʹnyĭ psikhologicheskiĭ zhurnal, 2023)
Background. Nowadays the issues of child upbringing have acquired special importance, which makes it crucial to update psychological and pedagogical research on the problem of personality development, to analyze and rethink theory and practice of forming ethical behavior in preschoolers, to search for solutions to the most challenging issues of moral development of children. Objective. [e article is devoted to E.O. Smirnova’s approach to the problem of upbringing in preschool, which was presented in her few works in the beginning of the 2000’s. Results. E.O. Smirnova’s views on the psychological foundations of moral education of preschoolers are based on the theoretical provisions of M.I. Lisina about the dual basis of interpersonal relationships between children — the object and the subject. Genuine moral behaviour is conditioned by the predominance of the subjective basis in the relationship to a peer, which is based on the perception of the other as a self-valuable person. [e balance between the two bases or the predominance of the subjective basis in interpersonal relations serves as the foundation for ethical behavior, but not for moral one. According to the views of E.O. Smirnova, in this case, children tend to follow ethical norms and rules, though only in speci\c situations when their behavior can be positively evaluated by peers or adults. Such ethical behavior is aimed at self-a]rmation of the child and increase in their self-esteem. Subject attitude towards a peer contributes to the transfer of ethical norms and rules into the real behaviour of the child. Following rules acquires the character of value: child cannot act otherwise. As L.S. Vygotsky wrote: “[e one who does not notice that he is acting morally acts morally.” Conclusions. [e theoretical approach to the problem of moral behavior in preschoolers served the basis for experimental work carried out under the guidance of E.O. Smirnova. [e study proved that to ensure genuine moral behavior the sense of communion and fellowship with others should become central issue in the upbringing of children. [is process involves removing \xation on themselves and their assessments, i.e., forming subjective attitude towards peers and adults. Practical application of the results. [e obtained results were used in practical work — a correctional and developmental programme aimed at providing a “special vision of the other” through the experience of living within a community and involvement with each other in real interaction was developed. Elena Olegovna Smirnova’s idea about the formation of subjective relationships as the main psychological condition of moral education might expand the possibilities of this approach application and extend it beyond the interpersonal relationships of children and their interaction with other people. “[e understanding of moral behavior is extremely expanding, because we acquire the right to talk not only about moral behavior in the narrow sense of the word, but also about the moral attitude to things, to oneself, to one’s body, etc.” (L.S. Vygotsky).